Positive electrode plate, preparation method thereof and sodium ion battery
A positive electrode plate combining layered transition metal oxide and polyanion compounds with controlled particle sizes and ratios addresses air stability and energy density issues, enhancing sodium ion battery performance.
Patent Information
- Application Number
- JP2023554324
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-11-29
- Filing Date
- 2022-12-09
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2042-12-09
AI Technical Summary
Existing sodium ion battery cathode materials face issues of poor air stability and low volumetric energy density due to limitations in layered transition metal oxides and polyanionic compounds, which affect battery performance and safety.
A positive electrode plate comprising a layered transition metal oxide and a polyanion compound, with controlled particle size distribution and mass ratio, is used to enhance air stability and electrochemical performance.
The solution improves air stability and electrochemical performance by optimizing the particle size relationship and mass ratio between the transition metal oxide and polyanion compound, resulting in higher pressing density and better electrochemical performance.
Smart Images

Figure 2025501034000001_ABST
Abstract
Description
[Technical field]
[0001] The present application relates to the technical field of batteries, and in particular to a positive electrode plate, its preparation method and a sodium ion battery.
[0002] CROSS REFERENCE TO RELATED APPLICATIONS This application claims priority based on a Chinese application filed with the China Patent Office on November 29, 2022, bearing application number 202211514774.7 and entitled "Positive electrode plate, its preparation method and sodium ion battery", the entire contents of which are incorporated herein by reference. [Background technology]
[0003] With the widespread application of lithium-ion batteries in the electric vehicle field, the demand for lithium resources has increased significantly. However, the reserves of lithium element in the earth's crust are only 0.0017%, and there has been no technology that can effectively recover lithium resources. The demand for large-scale energy storage and the demand in fields such as electric vehicles cannot be met. Therefore, in terms of the sustainable development and use of energy sources, it is important to find a new secondary battery system that is low cost, safe, and has a long cycle life. The reserves of sodium element in the earth's crust account for about 2.36% (mass fraction), which is much higher than the reserves of lithium element, and sodium element is widely distributed and low cost. And sodium and lithium are homologous elements, and no matter which one is used, the battery will be "rocking chair type" electrochemical charge and discharge during work. For this reason, the development of high-performance, low-cost sodium-ion battery technology is important for the sustainable development of fields such as large-scale energy storage and electric vehicles.
[0004] At present, the most promising sodium ion battery positive electrode materials mainly include layered transition metal oxides and polyanion compounds. Layered transition metal oxides have a higher specific capacity, which can better meet the requirements for high energy density, but they have poor air stability and are prone to ion exchange reaction with hydrogen ions of water molecules in air, which generates alkaline oxides such as Na2CO3, NaHCO3 and NaOH on the surface of the material, which directly absorbs water molecules to form interlayer crystal water, which changes the crystal structure of the material, reduces the crystallinity of the material, and the binder is defluorinated and ineffective due to the relatively strong alkaline environment formed on the surface of the material, and the alkali corrodes the aluminum foil of the current collector with amphoteric metal properties, which greatly impairs the performance of the battery. In the past, the common solution in the industry was to make the layered transition metal oxide of the material into micron-order polycrystalline or single-crystalline particles, and then improve it by doping or coating, but the air stability of the material cannot be effectively improved. Polyanion compounds have been attracting attention due to their stable framework structure, excellent cycle performance, and excellent air stability, but their poor intrinsic electronic conductivity limits their large-scale use. Currently, the main methods for improving them are nano-sizing and carbon composites, but when these methods are used, the volumetric energy density of the material decreases.
[0005] It is with this in mind that the present application has been devised. Summary of the Invention
[0006] One of the objectives of the present application is to provide a positive plate that solves the technical problems of poor air stability and low volumetric energy density of the positive plate in the prior art.
[0007] Another object of the present application is to provide a method for preparing said positive plate.
[0008] Another object of the present application is to provide a sodium ion battery.
[0009] In order to achieve the above objectives of this application, the following technical solutions are adopted. The positive electrode plate includes a current collector and a positive electrode material layer formed on at least one surface of the current collector. The positive electrode material layer includes a layered transition metal oxide and a polyanion compound. The chemical formula of the layered transition metal oxide is Na x The polyanion compound contains at least one of Fe, Mn, Cr, Ni, Co, Cu, Mg, Zr and Ti, and the chemical formula of the polyanion compound is NaAPO4, Na y A contains at least one of Fe and Mn, y satisfies 1≦y≦4, E contains at least one of V, Fe, Ni, Mn and Ti, X contains at least one of P, S and Si, and Q contains at least one of Fe, Mn and Co; and the mass ratio of the layered transition metal oxide to the polyanion compound is
number
number
number
[0010] In one embodiment, the range of ρ1 is 4.4 to 4.65 g / cm 3 and the range of ρ2 is 2.5 to 3.5 g / cm 3 It is.
[0011] In one embodiment, the layered transition metal oxide has a particle size D50 of 4 to 12 μm.
[0012] In one embodiment, the layered transition metal oxide has a particle size D10 of 1.27 to 3.82 μm.
[0013] In one embodiment, the particle size D' of the polyanionic compound 50 is 0.41 to 1.24 μm.
[0014] In one embodiment, the positive electrode layer further includes a conductive agent and a binder.
[0015] In one embodiment, the conductive agent comprises at least one of carbon nanotubes, conductive carbon black, conductive graphite, graphene, and carbon fibers.
[0016] In one embodiment, the binder comprises polyvinylidene fluoride.
[0017] In one embodiment, the total mass of the conductive agent and the binder is 5% or less of the mass of the positive electrode material layer.
[0018] In one embodiment, in the positive electrode layer, the mass ratio of the conductive agent to the binder is (1.5 to 3.5):(1.5 to 3.5).
[0019] In one embodiment, the press density of the positive electrode plate is 3.0 to 3.6 g / cm 3 It is.
[0020] The method for preparing the positive electrode plate includes the steps of preparing a positive electrode slurry containing a layered transition metal oxide and a polyanion compound, and applying the positive electrode slurry to at least one surface of the current collector, drying, and pressing.
[0021] In one embodiment, the positive electrode slurry further includes a conductive agent, a binder, and a solvent.
[0022] In one embodiment, the method for preparing the positive electrode slurry includes the steps of dissolving the binder in the solvent, adding and uniformly mixing a conductive agent to obtain a conductive slurry, and uniformly mixing the conductive slurry, the layered transition metal oxide, and the polyanion compound to obtain a positive electrode slurry.
[0023] In one embodiment, the drying temperature is 75 to 120°C.
[0024] In one embodiment, the pressure used in the press is 20 to 100 MPa.
[0025] A sodium ion battery includes the positive electrode plate.
[0026] Compared with the prior art, the present application has the following beneficial effects:
[0027] (1) In the present application, by controlling the particle size relationship, particle size distribution, and mass ratio relationship between the transition metal oxide and the polyanion compound, the obtained positive electrode plate has effectively improved air stability, higher press density, and excellent electrochemical performance.
[0028] (2) The method for preparing the positive electrode plate according to the present application is simple and easy to carry out, and involves applying a positive electrode slurry containing a layered transition metal oxide and a polyanion compound to at least one surface of a current collector, followed by drying and pressing.
[0029] (3) The sodium ion battery according to the present application has excellent electrochemical performance. [Brief description of the drawings]
[0030] In order to more clearly describe the specific embodiments of the present application or the technical solutions in the prior art, the drawings used in the specific embodiments or the prior art are briefly described below. It should be noted that the drawings described only show some embodiments of the present application. Those skilled in the art can obtain other drawings based on these drawings without using inventive ability. [Figure 1] FIG. 2 is a discharge curve diagram of a battery cell according to Example 1 of the present application. [Diagram 2] FIG. 11 is a cycle retention rate curve diagram of a battery cell according to Example 3 of the present application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] The present application will be described in detail with reference to the following examples. As those skilled in the art will appreciate, the following examples are merely for the purpose of illustrating the present application, and are not intended to limit the scope of the present application. In the examples, the specific conditions are not specified, and may be carried out under conventional conditions or conditions recommended by the manufacturer. For reagents or equipment whose manufacturers are not specified, conventional products available on the market may be used.
[0032] The positive electrode plate includes a current collector and a positive electrode material layer formed on at least one surface of the current collector, and the positive electrode material layer includes a layered transition metal oxide and a polyanion compound.
[0033] The chemical formula of the layered transition metal oxide is Na x It contains MO2, x satisfies 0.6≦x≦1.0, and M contains at least one of Fe, Mn, Cr, Ni, Co, Cu, Mg, Zr, and Ti.
[0034] The chemical formula of the polyanion compound is NaAPO4, Na y The binder contains at least one of E2(XO4)3 and Na2QP2O7, A contains at least one of Fe and Mn, y satisfies 1≦y≦4, E contains at least one of V, Fe, Ni, Mn and Ti, X contains at least one of P, S and Si, and Q contains at least one of Fe, Mn and Co. The mass ratio of the layered transition metal oxide to the polyanion compound (the layered transition metal oxide / the polyanion compound) is
number
number
number
[0035] In the present application, by controlling the particle size relationship, particle size distribution, and mass ratio relationship between the transition metal oxide and the polyanion compound, the obtained positive electrode plate has effectively improved air stability, higher press density, and excellent electrochemical performance.
[0036] True density refers to the actual mass of a solid substance per unit volume of a material in a completely sealed state, that is, the density excluding internal voids or gaps between particles. For the measurement method, refer to GB / T 24586-2009.
[0037] When multiple types of layered transition metal oxides are selected, ρ1 is the average value of the true densities of the multiple types of layered transition metal oxides, and when multiple types of polyanion compounds are selected, ρ2 is the average value of the true densities of the multiple types of polyanion compounds.
[0038] The mechanism of the present application includes the following: Assuming that all particles are spherical particles, and classifying the particles in order of size into primary, secondary, tertiary, quaternary, etc., the spherical particles are closely packed, the secondary particles are packed between the primary particles, the tertiary particles are packed between the primary and secondary particles, and other particles are packed in this manner. The porosity of the primary particles is about 38%, the porosity of the secondary particles is about 15%, the porosity of the tertiary particles is about 5%, and the porosity of the quaternary particles is about 2.0%. Even if smaller particles are added after the three levels of different sizes have been formed, the porosity cannot be significantly reduced to increase the volume density of the particles. Therefore, the present application is based on the deposition of three levels of particles, and three levels of particles are filled and deposited such that D50 of the transition metal oxide is the particle size of the primary particles, D10 of the transition metal oxide is the particle size of the secondary particles, and D50 of the polyanion compound is the particle size of the tertiary particles. The sizes of the secondary particles and the tertiary particles can be calculated based on the size of the primary particles. The combination of the three levels of particles (D50 of the transition metal oxide, D10 of the transition metal oxide and D50 of the polyanion compound) can effectively increase the deposition density (corresponding to the press density / volume density of the electrode plate).
[0039] After obtaining the particle size of each level, in order to improve the sensitivity of the layered transition metal oxide to air, it is necessary to distribute at least the polyanion compound in the electrode plate uniformly on the outer layer of the layered oxide to block the contact of the layered transition metal oxide with air. Assuming that all particles are spherical, the D50 of the transition metal oxide and the D50 of the polyanion compound are each taken as the average particle size, and the surface area of the corresponding metal oxide spherical particle can be calculated. To obtain the desired effect (the transition metal oxide is covered in the center by the polyanion compound), the polyanion compound is further assumed to be spherical, and the sum of the surface areas of all the spheres is equal to or greater than the surface area of the layered oxide, so that the particle number relationship between the two can be obtained based on the areas of the two, and the mass relationship between the two materials can be obtained based on the particle size, particle number, and true density of the two.
[0040] Therefore, by controlling the parameters such as particle size distribution and mass ratio, the press density can be increased and the sensitivity of the material to air can be reduced, and the press density can be increased while reducing the voids to a certain extent, thus suppressing the contact between the metal oxide and air. Metal oxides have high capacity and poor cycle performance, while polyanion compounds have low capacity and good cycle performance. By combining metal oxides with some polyanion compounds as the main component, it is possible to ensure a relatively high capacity and improve the cycle performance. In one embodiment, the particle size D' of the polyanionic compound 50 teeth,
number
[0041] In one embodiment, x includes, but is not limited to, 0.6, 0.7, 0.8, 0.9, or 1.0. The chemical formula of the layered transition metal oxide is NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, NaNi 1 / 3 Fe 1 / 3 Mg 1 / 3 O2, NaNi 1 / 5 Fe 2 / 5 Mn 2 / 5 O2, NaNi 1 / 3 Fe 1 / 3 Ti 1 / 3 O2, NaNi 3 / 9 Fe 3 / 9 Mn 2 / 9 Zr 1 / 9 O2, Na 0.9 Cu 0.25 Fe 0.3 Mn 0.45 O2, Na 2 / 3 Ni 1 / 3 Mn 5 / 6 Ti 1 / 6 O2, Na 0.75 MnO2, Na 2 / 3 Mn 2 / 3 Ni 1 / 3 O2, Na 2 / 3 Mn 5 / 9 Ni 3 / 9 Cr 1 / 9O2 or NaNi 1 / 5 Fe 1 / 5 Cu 1 / 5 Mn 2 / 5 Includes O2, etc.
[0042] In one embodiment, the polyanionic compound NaAPO4 is NaFePO4 or NaMnPO4. 。 In one embodiment, Na y In E2(XO4)3, y includes, but is not limited to, 1, 2, 3, and 4. y E2(XO4)3 can be NaV2(PO4)3, NaFe2(PO4)3, NaNi2(PO4)3, NaTi2(PO4)3, NaV2(SO4)3, NaV2(SiO4)3, etc. In one embodiment, Na2QP2O7 is Na2FeP2O7, Na2MnP2O7, Na2CoP2O7.
[0043] In one embodiment, the range of ρ1 is 4.4 to 4.65 g / cm 3 For example, 4.5 g / cm 3 , 4.52g / cm 3 or 4.6 g / cm 3 The range of ρ2 is 2.5 to 3.5 g / cm 3 For example, 2.64 g / cm 3 , 2.72g / cm 3 , 2.8g / cm 3 , 3g / cm 3 or 3.2 g / cm 3 And so on.
[0044] In one embodiment, ρ1 / ρ2 includes, but is not limited to, 1.3, 1.4, 1.46, 1.5, 1.52, 1.6, or 1.8, etc.
[0045] In one embodiment, the particle size D50 of the layered transition metal oxide is 4 to 12 μm, for example, 5.03 μm, 6.87 μm, 7.4 μm, 8 μm, 9 μm, or 10 μm.
[0046] In one embodiment, the particle size D10 of the layered transition metal oxide is 1.27 to 3.82 μm, for example, 1.3 μm, 1.52 μm, 1.83 μm, 2.44 μm, 2.5 μm, 2.8 μm, 3 μm, 3.15 μm, 3.5 μm, or 3.76 μm.
[0047] In one embodiment, the particle size D' of the polyanionic compound 50 is 0.41 to 1.24 μm, for example, 0.44 μm, 0.51 μm, 0.62 μm, 0.7 μm, 0.9 μm, 1 μm, or 1.2 μm.
[0048] In one embodiment, the positive electrode layer further includes a conductive agent and a binder.
[0049] In one embodiment, the conductive agent includes at least one of carbon nanotubes (CNT), conductive carbon black (SP), conductive graphite, graphene, and carbon fiber. In one embodiment, the conductive agent is conductive carbon black and carbon nanotubes, and the mass ratio of the conductive carbon black to the carbon nanotubes is (1 to 3):0.5, such as 1:0.5, 1.5:0.5, 2:0.5, 2.5:0.5, and 2.8:0.5.
[0050] In one embodiment, the binder comprises at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene, polypropylene acid, polyacrylonitrile, styrene-butadiene rubber, and polyimide.
[0051] In one embodiment, the total mass of the conductive agent and the binder is 5% or less of the mass of the positive electrode material layer, for example, 0.5%, 0.8%, 1%, 1.5%, 2%, 3%, 4%, 4.8%, etc. In one embodiment, the total mass of the conductive agent and the binder is 1% to 4.8% of the mass of the positive electrode material layer.
[0052] In one embodiment, in the positive electrode layer, the mass ratio of the conductive agent to the binder is (1.5 to 3.5):(1.5 to 3.5), for example, 1.5:3.5, 2:3, or 3.5:1.5.
[0053] In one embodiment, the press density of the positive electrode plate is 3.0 to 3.6 g / cm 3 For example, 3.1 g / cm 3 , 3.2g / cm 3 , 3.3g / cm 3 , 3.4g / cm 3 , 3.5g / cm 3 And so on.
[0054] In another aspect of the present application, the present application further provides a method for preparing the positive electrode plate, the method including the steps of preparing a positive electrode slurry containing a layered transition metal oxide and a polyanion compound, and applying the positive electrode slurry to at least one surface of the current collector, followed by drying and pressing.
[0055] The method for preparing the positive electrode plate according to the present application is simple and easy to carry out, and involves applying a positive electrode slurry containing a layered transition metal oxide and a polyanion compound to at least one surface of a current collector, followed by drying and pressing.
[0056] In one embodiment, the current collector according to the present application is an aluminum foil or a composite aluminum foil.
[0057] In one embodiment, the positive electrode slurry further includes a conductive agent, a binder, and a solvent. In one embodiment, the solvent includes N-methylpyrrolidone (NMP).
[0058] The method for preparing the positive electrode slurry specifically includes the steps of dissolving a binder in a solvent, adding and uniformly dispersing a conductive agent to obtain a uniform conductive slurry, and adding and uniformly dispersing a layered transition metal oxide and a polyanion compound to the conductive slurry to obtain a positive electrode slurry.
[0059] In one embodiment, the drying temperature is 75 to 120° C. In one embodiment, the drying temperature is 80° C., 90° C., 95° C., 100° C., 110° C., or 115° C., etc.
[0060] In one embodiment, the pressure used in the press is 20 to 100 MPa. In one embodiment, the pressure used in the press is 30 MPa, 40 MPa, 50 MPa, 60 MPa, 70 MPa, 80 MPa, 90 MPa, 95 MPa, etc.
[0061] In another aspect of the present application, the present application further provides a sodium ion battery, the sodium ion battery including the positive electrode plate, and the sodium ion battery according to the present application has excellent electrochemical performance.
[0062] The present invention will be further interpreted and explained below with reference to specific examples and comparative examples.
[0063] The discharge curve diagram of the battery cell according to Example 1 of the present application is shown in FIG.
[0064] The cycle retention curve of the battery cell according to Example 3 of the present application is shown in FIG. EXAMPLES
[0065] The method for preparing the positive plate includes the following steps:
[0066] (a) 2.0 parts by mass of PVDF was dissolved in NMP solvent, and 2.0 parts by mass of SP and 0.5 parts of CNT were added as conductive agents and uniformly dispersed to obtain a conductive slurry S1.
[0067] (b) Layered transition metal oxide NaNi as a positive electrode material 1 / 3 Fe 1 / 3 Mn 1 / 3 75.5 parts by mass of O2 and 20.0 parts by mass of a polyanion compound Na3V2(PO4)3 as a positive electrode material are added to the first conductive slurry of step (a) and uniformly dispersed to obtain a slurry S2, and NaNi1 / 3 Fe 1 / 3 Mn 1 / 3 O2 is D 10 = 2.44 μm, D 50 = 6.87μm and true density is 4.50g / cm 3 The positive electrode material Na3V2(PO4)3 is D 50 = 0.51 μm and true density is 3.24 g / cm 3 It was.
[0068] (c) The above slurry S2 was uniformly applied to an aluminum foil, which was then heated and dried, and rolled to obtain a positive electrode plate.
[0069] A battery was assembled using the positive electrode plate according to this embodiment, a negative electrode, a separator, an electrolyte, and the like, and then subjected to processes such as aging, chemical formation, and aging to obtain a battery cell to be measured. EXAMPLES
[0070] The preparation method of the positive electrode plate was different from that of Example 1 only in that the layered transition metal oxide was 88 parts by mass and the polyanion compound was 7.5 parts by mass, and the other conditions were the same as those of Example 1. EXAMPLES
[0071] Regarding the preparation method of the positive electrode plate, the layered transition metal oxide is Na 0.9 Cu 0.25 Fe 0.3 Mn 0.45 O2 and particle size D 10 = 1.83 μm, and particle size D 50 = 5.03μm and true density is 4.55g / cm 3 The only difference from Example 1 was that the temperature was 100° C., and the other conditions were the same as those of Example 1. EXAMPLES
[0072] Regarding the preparation method of the positive electrode plate, the polyanion compound is NaFePO4, and the particle size is D 50 = 0.44μm and true density is 3.14g / cm 3The only difference from Example 1 was that the temperature was 100° C., and the other conditions were the same as those of Example 1. EXAMPLES
[0073] Regarding the preparation method of the positive electrode plate, the layered transition metal oxide is NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 and Na 0.9 Cu 0.25 Fe 0.3 Mn 0.45 and the polyanion compound includes NaFePO, NaV(PO), and NaMnP0 in a mass ratio of 1:1:1. The true density of NaMnP0 is 3.26 g / cm. 3 The only difference from Example 1 was that the temperature was 100° C., and the other conditions were the same as those of Example 1.
[0074] [Comparative Example 1] The method for preparing the positive plate includes the following steps:
[0075] (a) 2.0 parts of PVDF was dissolved in NMP solvent, and 2.0 parts of SP and 0.5 parts of CNT were added as conductive agents and uniformly dispersed to obtain a conductive slurry S1.
[0076] (b) Layered transition metal oxide NaNi as a positive electrode material 1 / 3 Fe 1 / 3 Mn 1 / 3 Add 95.5 parts of O2 to S1 and disperse it uniformly to obtain slurry S2. 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 is D 10 = 2.44 μm, D 50 =6.87 μm.
[0077] (c) The above slurry S2 was uniformly applied to an aluminum foil, which was then heated and dried, and rolled to obtain a positive electrode plate.
[0078] A battery was assembled from the positive electrode plate according to this comparative example, a negative electrode, a separator, an electrolyte, and the like, and then subjected to processes such as aging, chemical conversion, and aging to obtain a battery cell to be measured.
[0079] [Comparative Example 2] The preparation method of the positive plate included the following steps.
[0080] (a) 2.0 parts of PVDF was dissolved in NMP solvent, and 2.0 parts of SP and 0.5 parts of CNT were added as conductive agents and uniformly dispersed to obtain a conductive slurry S1.
[0081] (b) 95.5 parts of a polyanion compound Na3V2(PO4)3 as a positive electrode material is added to S1 and uniformly dispersed to obtain a slurry S2. 50 =0.51 μm.
[0082] (c) The above slurry S2 was uniformly applied to an aluminum foil, which was then heated and dried, and rolled to obtain a positive electrode plate.
[0083] A battery was assembled from the positive electrode plate according to this comparative example, a negative electrode, a separator, an electrolyte, and the like, and then subjected to processes such as aging, chemical conversion, and degeneration to obtain a battery cell to be measured.
[0084] [Comparative Example 3] Regarding the preparation method of the positive electrode plate, the layered transition metal oxide is made of a material with a particle size of D 10 = 2.8 μm, particle size D 50 = 15μm and true density is 4.49g / cm 3 and the polyanionic compound has a particle size D 50 = 1.65μm and true density is 3.25g / cm 3 The only difference from Example 1 was that the temperature was 100° C., and the other conditions were the same as those of Example 1.
[0085] [Experimental Example] Electrochemical performance tests were carried out on the positive electrode plates and sodium ion batteries of the examples and comparative examples by the following method.
[0086] 1. Residual alkali measurement The positive plate was stored in an environment with a humidity of 26±3% for 12 hours, and the powder material in the plate was separated from the aluminum foil and transferred to a beaker, added with deionized water, stirred for 60 seconds, filtered, and the filtrate was transferred to the sample stage of a potentiometric titrator and subjected to potentiometric titration using hydrochloric acid. The carbonate ion and bicarbonate ion obtained by the measurement were converted into the content of sodium ion. The content calculation basis was the mass of layered transition metal oxide in the positive electrode powder material after separation from the aluminum foil.
[0087] 2. Capacity measurement The battery was charged at a constant current and constant voltage of 0.5 C up to 4.0 V, with a final current of 0.05 C. The battery was left to stand for 30 minutes, and then discharged at a constant current of 0.5 C down to 2.0 V. The battery capacity was recorded, and was converted to capacity per gram based on the mass of the active material in the positive plate and recorded as reversible capacity.
[0088] 3. Cycle performance measurement The battery was charged at a constant current and constant voltage of 45±2°C at a rate of 0.5C up to 4.0V, with a final current of 0.05C, and allowed to stand for 30 minutes. It was then discharged at a constant current of 0.5C up to 2.0V, and allowed to stand for 30 minutes. This cycle was repeated 500 times, and the ratio of the 500th capacity to the initial capacity was recorded and recorded as the capacity retention rate.
[0089] The measurement results are shown in Table 1.
[0090] [Table 1]
[0091] As can be seen from Table 1, in each embodiment of the present application, the layered transition metal oxide with a large particle size and the polyanion compound with a small particle size are filled with each other, and the polyanion compound is the main component, and the conductive agent and binder are the auxiliary components, and are uniformly dispersed on the surface of the layered transition metal oxide. In this way, on the one hand, the press density of the positive plate is higher, and the energy density of the battery can be effectively increased, and on the other hand, the positive plate obtained by the composite has better air stability and cycle performance.
[0092] In contrast to Example 1, the positive electrode plate obtained in Comparative Example 1, in which only a layered transition metal oxide was used as the active material, had a low press density and a low retention rate after 500 cycles.
[0093] In contrast to Example 1, the positive electrode plate obtained in Comparative Example 2, in which only a polyanion compound was used as the active material, had a low press density and a low reversible capacity.
[0094] Compared with Example 1, the particle size distribution of the active material according to Comparative Example 3 was not within the scope of protection of the present application, and the obtained positive electrode plate had a low press density and a low cycle retention rate.
[0095] The above embodiments are merely for illustrating the technical solutions of the present application, and are not intended to limit the same. Although the present application has been described in detail with reference to the above embodiments, those skilled in the art may modify the technical solutions described in the above embodiments, and may make equivalent substitutions for some or all of the technical features therein. These modifications or substitutions do not deviate from the essence of the corresponding technical solutions and the scope of the technical solutions of the embodiments of the present application.
Claims
1. A current collector and a positive electrode material layer formed on at least one surface of the current collector, the positive electrode layer contains a layered transition metal oxide and a polyanion compound, The chemical formula of the layered transition metal oxide is Na x M.O. 2 Including, x satisfies 0.6≦x≦1.0, M includes at least one of Fe, Mn, Cr, Ni, Co, Cu, Mg, Zr, and Ti; The chemical formula of the polyanion compound is NaAPO 4 , Na y E 2 (X.O. 4 ) 3 and Na 2 QP 2 O 7 At least one of A contains at least one of Fe and Mn, y satisfies 1≦y≦4, E contains at least one of V, Fe, Ni, Mn, and Ti; X contains at least one of P, S and Si; Q contains at least one of Fe, Mn, and Co; The mass ratio of the layered transition metal oxide to the polyanion compound is [0010] and ρ 1 is the true density of the layered transition metal oxide, ρ 2 is the true density of the polyanionic compound, ρ 1 / ρ 2 ρ is 1.25≦ρ 1 / ρ 2 ≦1.86 is satisfied, The particle size distribution of the layered transition metal oxide is [0025] Fulfilling The particle size D' of the polyanion compound 50 teeth, [0030] Fulfill A positive electrode plate characterized by:
2. Said ρ 1 The range is 4.4 to 4.65 g / cm 3 and Said ρ 2 The range is 2.5 to 3.5 g / cm 3 is The positive electrode plate according to claim 1 .
3. (1) The particle size D50 of the layered transition metal oxide is 4 to 12 μm; (2) the particle diameter D10 of the layered transition metal oxide is 1.27 to 3.82 μm; (3) Particle size D′ of the polyanion compound 50 is 0.41 to 1.24 μm; The present invention includes at least one of the following characteristics (1) to (3): The positive electrode plate according to claim 1 .
4. (1) the positive electrode layer further includes a conductive agent and a binder; (2) The conductive agent includes at least one of carbon nanotubes, conductive carbon black, conductive graphite, graphene, and carbon fibers; (3) The binder contains at least one of polyvinylidene fluoride, polytetrafluoroethylene, polypropylene acid, polyacrylonitrile, styrene-butadiene rubber, and polyimide; (4) the total mass of the conductive agent and the binder is 5% or less of the mass of the positive electrode material layer; (5) In the positive electrode layer, the mass ratio of the conductive agent to the binder is (1.5 to 3.5):(1.5 to 3.5); The present invention includes at least one of the features (1) to (5). The positive electrode plate according to claim 1 .
5. The press density of the positive electrode plate is 3.0 to 3.6 g / cm 3 is The positive electrode plate according to claim 1 .
6. preparing a positive electrode slurry comprising a layered transition metal oxide and a polyanion compound; applying the positive electrode slurry to at least one surface of the current collector, and drying and pressing the positive electrode slurry. The method for preparing a positive electrode plate according to any one of claims 1 to 5.
7. The positive electrode slurry further includes a conductive agent, a binder, and a solvent. The method for preparing a positive electrode plate according to claim 6 .
8. dissolving the binder in the solvent, adding a conductive agent and mixing uniformly to obtain a conductive slurry; and uniformly mixing the conductive slurry, the layered transition metal oxide, and the polyanion compound to obtain a positive electrode slurry. The method for preparing a positive electrode plate according to claim 7.
9. (1) The drying temperature is 75 to 120° C.; (2) the pressure used in the press is 20 to 100 MPa; The present invention includes at least one of the following characteristics (1) to (2): The method for preparing a positive electrode plate according to claim 6 .
10. The positive electrode plate according to any one of claims 1 to 5 is included. A sodium ion battery characterized by:
Citation Information
Patent Citations
Composite positive electrode material, sodium ion battery positive plate and sodium ion battery
CN115000374A
Positive electrode material for sodium ion battery and preparation method of positive electrode material
CN115241422A
Electrode active material, electrode, and sodium secondary battery
JP2011134551A
Positive electrode material for sodium secondary battery, manufacturing method thereof, sodium secondary battery electrode using the positive electrode material for sodium secondary battery, nonaqueous sodium secondary battery having the sodium secondary battery electrode, and electric device having the nonaqueous sodium secondary battery incorporated therein
JP2013175311A
Nonaqueous electrolytic secondary battery
JP2014072049A